Peculiarities of state-public school management - Shorobura, I. (Journal of Education, Health and Sport, 2022)
The article analyzes the features of public administration of the school. Today, a school cannot exist separately from the needs and interests of the community, but it can be a driver of its development and implementation. In this case, the model of a socially active school can be effective, which aims not only to provide educational services to students, but also to develop the community, involve parents and community members in solving social and other problems that exist in the school. and in the community. The management of socially active schools is based on partnership and volunteer relations, namely the management is carried out on the basic principles of: democracy; prognosticity; adaptability; flexibility and mobility; focus on development, innovation, creativity; personality-oriented and individual approach. The model of activity of an educational institution as a socially active school includes three components, namely: democratization; volunteering; mutually beneficial partnership in the school-community system, which is implemented through project activities of all participants in the educational process. An important role belongs to the educational district.The growing influence of parents and the public contributes to the creation of public administration bodies, namely the School Board, the Board of Trustees, the Public School Fund, and the Alumni Association. Public authorities of the school consider strategic issues of school development and exercise public control. In the formation of the model of public administration of educational institutions of great importance should be given to work with parents of students. Today, public school bodies are being actively created. They approve strategic development plans, have the opportunity to exercise public control over its work.